Testis sparing surgery in the treatment of bilateral testicular germ cell tumors and solitary testicle tumors: A single institution experience. Issue 2 (5th September 2014) - Bojanic, Nebojsa; Bumbasirevic, Uros; Vukovic, Ivan; Bojanic, Gordana; Milojevic, Bogomir; Nale, Djordje; Durutovic, Otas; Djordjevic, Dejan; Nikic, Predrag; Vuksanovic, Aleksandar; Tulic, Cane; Micic, Sava
<x xml:space="preserve">Abstract</x> Background and Objective To assess the oncologic and functional outcomes of testicular sparing surgery (TSS) based on a single institution experience. Methods Forty‐one patients with bilateral and 3 patients with solitary testicle tumors were referred to our institution. The inclusion criteria for TSS were normal serum testosterone levels, and tumor size (<2 cm). Sperm analysis and hormone status evaluation were performed preoperatively and postoperatively. None of the patients underwent local radiation therapy following TSS for reasons of fertility preservation. Results A total of 26 TSS were performed in 24 patients. The median follow‐up period was 51.0 months. Seven patients developed local recurrence, of which 5 had TIN and were subjected to radical orchiectomy, whereas re‐do TSS was done in remaining 2 patients. The overall survival of the study group was 100%, and the presence of testicular intraepithelial neoplasia (TIN) was associated with worse recurrence‐free survival (P = 0.031, log‐rank). Testosterone values were normal in all of the patients, while 4 patients achieved conception. Conclusions TSS is acceptable from an oncological point of view, and it enables continuation of a patient's life without lifelong hormonal substitution. Additionally, local irradiation therapy could be delayed in patients with TIN who wish to father children, but with high local recurrence rate. J. Surg. Oncol. 2015 111:226–230. © 2014 Wiley Periodicals, Inc.